EVALUATION OF WEB-BASED POLAC-D APPLICATION (ACEH-DJJ HEALTH POLYTECHNIC) - Cut Yuniwati; Fithriany Fithriany; Cut Nurhasanah (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Maternal and child health is a national policy which is one of the strategic plans that is about making pregnancy safer. One of the main strategies being implemented is to increase access to and reach of quality maternal and neonatal health services to reduce maternal and infant mortality. PolAc-D is a web-based application that has been designed to monitor the health of pregnant women and fetuses. The purpose of this study was to evaluate the use of the PolAc-D application. The research method is a survey with a questionnaire that has been tested for validity and reliability, the sample used is all midwives in the working area of the Langsa Baro Health Center, totaling 47 people. The results of the study obtained a total score of 2,136, an average score of 45.4, for a maximum score of 53 and a minimum score of 39. These results mean that the evaluation of the use of the PolAc-D application is very good, both in terms of use, application features that are easy to understand and according to the services carried out every day by midwives in providing services.